LANGUAGE LEARNING STRATEGIES APPLIED BY ENGLISH DEPARTMENT STUDENTS TO IMPROVE ENGLISH SKILLS - Mike Amelia (Universitas Mahaputra Muhammad Yamin, 2019)
The aim of this research is to describe languange learning strategies used by skillfull students to improve english skills:Speaking ,Writing, Reading and Listening. This reseacrh used descriptive qualitative method. The participant of this research were the skillfull students who got A in English skill subject.It consist of: 3 student (speech and debate class), 9students( paper/Thesis Writing class), 20 students(Extensive Reading class), 11 students (listening comprehension II class). This research used Purposive Random sampling technique. The instrumentation of this research were questionaire and interview. The were some result of thi research: First, speaking skill. Based on the result of questionnaire it was found that students used six types of language learning strategy: cognitive strategy, metacognitive strategy, memory-related strategy, compensation strategy, affective strategy and social strategy and based on interview, there were some learning strategies used by the students such as practice speaking outside the classroom,repeat the dialoge from native speaker, guessing intelligently and overcoming limitations, lowering anxiety by practice with friends. Second, Writing Skill. Based on the result of questionnaire, the most frequently used by skillful students was cognitive strategies and followed by compensation strategies , affective strategies, metacognitive strategies , social strategies , and at least strategy used by skillful students was memory strategies .Furthermore, factors influence the choice of language learning strategies were associating, placing new words into a context, translating, summarizing, selecting topic, using synonym, planning for language task, self-evaluation, discussing feeling with friends, asking for correction. Third, Reading Skill. Based on questionnaire,there were metacognitive strategies (planning, monitoring, and evaluation), cognitive strategies (summarizing, imagery, audiotory representation, making inference, using resources, note-taking, and elaborating of prior knowledge) social strategies (cooperating, clarifying, and self-talk). Factors influencing the choice of language learning strategy were motivation, age and gender, learning style, situation of the classroom, and belief on language learning.Fourth, Listening skill, There were some learning strategie used: affective strategies (feelings), compensatory strategies (guessing from the context), memory-related strategies (choosing position), social strategies (asking for help, social norms), cognitive strategies (note taking, practice), and metacognitive strategies (learning style, learning needs, planning, monitoring mistakes, evaluation).